Methodology to Generate Strategic Manufacturing Indicators to Support Decision-Making–Case Study of a Food Company - Quezada-Valenzuela, F; Aballay-Fredes, C; Vargas-Guzman, M (Taylor and Francis Ltd., 2024)
This study proposes a methodology that selects key performance indicators and measures their influence on the strategic manufacturing objectives of a food company. The proposed hybrid methodology used the focus model centered on a value function to select criteria and classify key performance indicators and the multi-criteria model DEMATEL to identify the level of influence of key performance indicators on strategic manufacturing objectives. This new method constructs a value function with input from all production line members. This allows the degree of direct and indirect influence of selected key performance indicators to be measured to achieve the organization’s strategic objectives. Finally, seven key performance indicators were selected, the most influential being the level of automation, performance, set-up times, and resource use. © 2024 American Society for Engineering Management.